Learning Al-Qur'an Hadith Using Study Tours to Improve Religious Moderation Attitudes and Socio-Cultural Literacy of Madrasah Aliyah Students - Zarkasi; Syamsul Ma’arif; Abdul Djamil; Ihsan; M. Afief Mundzir; Alfina Wildatul Fitriyah; Mochamad Tholib Khoiril Waro; Abdullah Hanapi (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – This research aims to analyze how learning steps using study tours can improve the religious moderation and socio-cultural literacy of Madrasah Aliyah students. Given increasing concerns about radicalism among adolescents, it is important to explore learning methods that are effective in shaping moderate attitudes and socio-cultural literacy. Design/methods/approach – This research uses a qualitative method with a phenomenological approach, while data is collected through observation, interviews, and documentation. The unit of analysis in this study is the XI grade students of Madrasah Aliyah MA Miftahussalam Demak, MANU Demak, and MA Sholahuddin Demak, who hold study tours to Puja Mandala, Bali, once every year. Findings – The results of this study explain that to improve the attitude of religious moderation and socio-cultural literacy of madrasah aliyah students in learning al-Qur'an hadith using study tours in Puja Mandala Bali are by curriculum preparation, identification of learning objectives, selection of tourist sites, preparation of learning materials, field experiences, interactive learning activities, learning evaluation, post-tour reinforcement, and collaboration with stakeholders. Research implications/limitations – This research is limited to only exemplifying the Puja Mandala as a tourist study object. Originality/value – Study tours are one solution to minimize and prevent radicalism and intolerance among students in Madrasah Aliyah. They can also improve religious moderation and socio-cultural literacy.